Effect of different contents of zirconia and yttrium oxide on microstructure and properties of high alumina ceramics. Issue 3 (23rd December 2019) - Huang, Bensheng; Fu, Sheng; Zhang, Shunshun; Lin, Anna; Guan, Zhongyi
Abstract: The effects of zirconia and yttrium oxide addition on microstructure, bulk density, microhardness, flexural strength, and wear resistance of high alumina ceramics (>97 wt% Al2 O3, MSA ceramics) composed of MgO–SiO2 –Al2 O3 system have been investigated. The results show that the addition of zirconia makes the mechanical properties and wear properties of ceramics composed of MgO–SiO2 –Al2 O3 –ZrO2 (MSAZ ceramics) system have been greatly improved compared with MSA ceramics. In addition, the ceramics composed of MgO–SiO2 –Al2 O3 –ZrO2 –Y2 O3 (MSAZY ceramics) system have better mechanical properties and wear properties than MSAZ ceramics. With the contents of zirconia and yttrium oxide increase, the bulk density, microhardness, and flexural strength of MSAZ and MSAZY ceramics increased at first and then decreased. However, the wear rate shows the opposite. When 0.4 wt% ZrO2 and 0.6 wt% Y2 O3 were added to the matrix, the wear rate of MSAZY ceramics reached a minimum of 0.042%, and the wear resistance was improved by about 73.8% compared with MSA ceramics with a wear rate of 0.16%. In addition, the optimum additions of zirconia and yttria are 0.4% and 0.6%, respectively.